Leadership Efforts in Improving the Five Work Cultures of Religious Affairs Ministry at the Religious Affairs Office of Kumun Debai District - Natardi, Natardi (Insight: Indonesian Journal of Social, Humanity, and Education, 2025)
This article aims to examine the role and efforts of leadership in enhancing the five work cultures of the Ministry of Religious Affairs at the Kumun Debai Subdistrict Religious Affairs Office. This article uses a qualitative research method with a case study. Data sources were obtained from primary and secondary data. The data collection methods used were observation, interviews, and documentation. The data analysis techniques used were data condensation, data presentation, and conclusion drawing. The results of the study showed that there was a gap between the current situation and the desired situation in the implementation of the five work cultures at the Kumun Debai Subdistrict Religious Affairs Office. This indicates that there are acute problems in all five work cultures. Therefore, the leadership’s efforts to improve the five work cultures of the Ministry of Religious Affairs at the Kumun Debai Subdistrict KUA are through efforts to develop the identity, attitudes, and behaviour of the apparatus; developing cooperation and work dynamics through improving public policy, improving the management system and community services, and increasing supervision and enforcement of discipline.